Analysis of the Silaba Method in Beginning Reading Activities for Class 1 at Banjarsari 01 Public Elementary School - Leni Fuzi Astuti (LADU: Journal of Languages and Education, 2023)
Background: Beginning reading is one of the most basic skills for students and as a tool to find out the meaning that has been learned in learning at school, beginning reading is one of the activity programs specifically designed for students who have just entered elementary school. The silaba method is a syllable method that presents words into syllables and then assembles syllables into words with the aim that students who are unable to read words can read words. Purpose: This study aims to determine whether the silaba method can improve the beginning reading activities of grade 1 students at SDN Banjarsari 01. Design and methods: This research uses a qualitative descriptive method, which is a qualitative descriptive method. The approach used in this study is a qualitative approach. This research was conducted at Banjarsari 01 Elementary School, Banjarsari Village, Ciawi District, Bogor Regency. The instrument used in this study was an interview guide instrument. The technique used in this study was a data collection technique, which in this study used data collection in the form of observation, interviews and documentation, the data analysis technique used in this study is an interactive data analysis technique in conducting data analysis with a model according to Milles and Huberman. Results: The results of this study indicate that the silaba method is a suitable method to be applied in beginning reading activities because it greatly facilitates students in reading skills for grade 1 students at SDN Banjarsari 01”. This silaba method also facilitates teachers in learning activities. The media needed by the teacher in this silaba method is quite simple and also easily understood by all students. Beginning reading for grade 1 students using the silaba method meets the indicator criteria for the achievement of students' reading activities.